Can Environmental Information Disclosure Improve Urban Green Economic Efficiency? New Evidence From the Mediating Effects Model - Lin, Shihai (Frontiers in Environmental Science, 2022)
Environmental information disclosure, as a command control type of environmental regulation, alleviates the information asymmetry of pollution sources between the government and enterprises, and plays an important role in promoting the development of urban green economy. It is obvious that existing studies often regard the relationship between Environmental Information Disclosure (EID) and urban green economy as “black-box”, in order analyze the transmission mechanism between them, based on the panel data of 113 cities in China from 2008 to 2018, this paper makes the following empirical research: Firstly, the Urban Green Economy Efficiency (UGEE) is calculated by using Data Envelopment Analysis model with undesirable output. Secondly, the panel data model and mediating effect model are employed to test the impact of environmental information disclosure on urban green economy efficiency and the possible mediating variables. The main conclusions are as follows: (1) From 2008 to 2018, the UGEE increased by about 9.94%, showing an upward trend. (2) EID significantly promotes UGEE, and the results of mediating effect model indicates that reduction of industrial pollution emissions and improvement of technological innovation are effective transmission paths, the proportion of mediating effect in the total effect is 0.367 and 0.579 respectively. (3) The relationship between EID and UGEE, EID and technological innovation exist “U-shaped” curve relationship; the relationship between EID and industrial pollution emissions shows “inverted U-shaped” curve. EID plays a role of “first inhibition, then promotion” in sustainable development. (4) The sustainability effect of EID is more obvious in industrial cities. Furthermore, robustness test and instrumental variable method support the above conclusions. This research provides a reference for how to lessen information asymmetry and reduce negative externalities in the formulation of environmental regulatory policies.